Asparaginase production by endophytic fungi from Thai medicinal plants: Cytoxicity properties - Teerayut Theantana (2018)
A total of 194 fungal endophytes were isolated from wild medicinal plants in Thailand. Cancer-inhibitory asparaginases from 15 selected endophytic strains were tested for their anti-proliferation activity against two cancer cell lines. The endophytic fungi were asparaginase sources which were devoid of glutaminase activity. In vitro experiments showed that asparaginase from the most important strain Colletotrichum sp. E5T9 completely decreased the survival rate of CaCo2 human Caucasian colon adenocarcinoma and decreased the survival rate of HepG2 human Caucasian hepatocyte carcinoma by 70%. When a crude culture of Colletotrichum sp. E5T9 was applied to the L929 connective tissue line, 42.66% and 44.32% cell viability resulted on first and second day, respectively. After the third day, the L929 connective tissue line, treated with Colletotrichum sp. E5T9 were able to grow at normal levels with more than 97% cell viability. ©IJIB, All rights reserved.